Key Components of Sustainable Supply Chain Development of the Agricultural Sector of Ukraine - Varchenko, O.; Utechenko, D.; Khakhula, L.; Slobodeniuk, O.; Byba, V.; Portyan, M.; Shepel, T. (ExcelingTech, 2019)
The article analyzes significant changes that have taken place in the development of the rural sector of Ukraine by sustainable supply chain development, which includes two components: agrarian (agriculture and technologically related industries) and rural areas (spatial base of production and resettlement of the population) of the second half of the last century. Current problems are revealed and the prospects of the rural sector functioning, through the prism of different concepts of productive forces development, are outlined. The problems are analyzed and prospects of rural sector functioning in various conceptions of productive forces development are outlined. The objective preconditions are outlined and the negative tendencies in the actions of the government bodies related to the agricultural sector in the conditions of the planned, transitional and market economy are revealed. The important role of the rural sector components, namely the rural economy and the living environment of the rural population, in the theory of complementary agrarian and rural development is substantiated. Thus, taking into account the negative tendency, economy development oriented to agriculture is seen in the following aspects: the diversity of industries and products, the placement of nonagricultural production facilities, regeneration of livestock sectors, the organization of crop products cultivation with a high proportion of manual labor, the introduction of agrarian logistics modern methods etc. At the same time, agricultural development is seen in solving the problems of the rural population through the use of the resource potential of the united territorial communities, as well as at the initiative of rural (domestic) communities in order to eliminate asymmetry and qualitative improvement of the living environment by increasing the availability of basic services for inhabitants of settlements which are not UTC centers (UTC – united territorial communities). It is proved that the state agrarian policy at the present stage should be based on scientifically grounded, balanced (or proportional, depending on the particular situation) and mutually reinforcing combination of two directions of its implementation – sectoral and territorial (or agrarian and rural development), that is, complementarity.